ANALISA MATRIKS KEKAKUAN PADA BALOK NON PRISMATIS DENGAN MENGGUNAKAN PRINSIP ELEMEN HINGGA - Christiani Chandra Manubulu (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2023)
In structural planning, planners often choose a uniform landscape across a stretch of structure. But sometimes for certain certain contour selection of non-prismatic views, it is necessary to analyze the rigour matrix on the non-prismatic beam to make it easier and faster for calculations in structural analysis. The prismatic beam viewer selected in this study is a simple beam at one long landscape but has a distinct geometric form and type of material. The results of this study are the results of the rigour structure for a non-prismatic beam affected by the value of modulus elasticity that describes the type of material, as well as the broad and long landscape that describes the geometry of a non-prismatic beam viewer.